Hematological Changes in Pre and Post Dialysis in Patients Undergoing Hemodialysis: A Comparative Study at Zawia Hospital - Fahima Albeshti,; Ayah AL-Hanish,; Hidya Altayyaib,; Maram Ahmed,; Ibtihaj Alajilani, (AlQalam Journal of Medical and Applied Sciences, 2024)
Chronic kidney disease (CKD) is a common condition that affects millions of people worldwide, and is responsible for high morbidity and mortality rates. The progression of CKD is associated with several serious complications and changes in blood composition. Thus, patients with CKD require dialysis to manage the disease. This study assessed the impact of haemodialysis on changes in pre and post haematological parameters in CKD patients. A cross-sectional study was carried out at Al-Zawiya Dialysis Hospital in Libya. Sixty patients with CKD were regularly undergoing haemodialysis three times a week. Data were analysed by SPSS 24.0 version. The study shows significant differences in blood parameters before-dialysis and after-dialysis levels. The mean WBC 6.22 × 10^3/µL to 6.03 × 10^3/µL, (p = 0.0045), the mean RBC 3.56 × 10^6/µL to 3.66 × 10^6/µL, (p = 0.001), the mean HCT in pre and post-haemodialysis was 32.01% to 32.71% (p = 0.018), the mean Haemoglobin 10.11 g/Dl in pre - dialysis to 10.32 g/dL post - dialysis (p = 0.027 ), the mean MCV 90.24 fL to 89.69 fL ,(p < 0.0001), the mean MCH in pre and MCH in pre and post-haemodialysis post- haemodialysis was 28.58 pg to 28.5 pg,(p < 0.0001), the mean MCHC in pre and post-haemodialysis (p = 0.003), and PLT was 241.08 × 10^3/µL to 240.46 × 10^3/µL in pre and post-haemodialysis, (p = 0.002). The different degrees of abnormality in haematological parameters in patients with renal disease under haemodialysis need careful evaluation and management. Routine assessment of these parameters is important in treatment and can help lower morbidity and mortality rates among these patients مرض الكلى المزمن هو حالة شائعة تصيب ملايين الأشخاص في جميع أنحاء العالم، وهو مسؤول عن ارتفاع معدلات الإصابة والوفيات، ويرتبط تطور مرض الكلى المزمن بعدد من المضاعفات الخطيرة، ويعزز التغيرات في معايير الدم، ويحتاج مرضى مرض الكلى المزمن إلى الغسيل الكلوي لضرورة استمرار حياتهم و تحسين ادائهم الوظيفي الا انها تترك اثارا سلبية علي المريض. هدفت هذه الدراسة إلى تقييم تأثير غسيل الكلى على التغيرات في معايير الدم قبل وبعد الغسيل لدى مرضى الفشل الكلوي المزمن. أجريت دراسة مقطعية بوحدة الكلى التابعة لمستشفى الزاوية في ليبيا، حيث تضمنت 60 مريضًا يعانون من امراض الكلى المزمنة ويخضعون بانتظام لغسيل الكلى ثلاث مرات في الأسبوع و تم إجراء الاحصاء الوصفي عن طريق قياس النسب باستخدام برنامجSPSS الإصدار 24.0 . أظهرت الدراسة وجود فروق في معايير الدم قبل الغسيل الكلوي ومستوياته بعد و اوضحت نتائج التحليل الإحصائي حدوث ارتفاعا طفيف في متوسط تركيز الصفائح الدموية قبل غسيل الكلى الي ما بعد الغسيل (p 0.002 –value) و يشمل هذا الارتفاع ايضا الهيموجلوبين و القيمة المتوسطة في مرضى ما قبل غسيل الكلى الي ما بعد الغسيل (0.027(P < value- و ارتفاع ضعيف في كريات الدم الحمراء وكان متوسط قيمة خلايا الدم الحمراء في ما قبل غسيل الكلى الي ما بعد الغسيل ( p 0.001 –value ) و وجد ارتفاع في متوسط تركيز الهيموجلوبين في كريات الدم الحمراء MCHC وكان متوسط قيمة MCHC في مرضى ما قبل غسيل الكلى الى ما بعد الغسيل (0.003 p) بينما كان الانخفاض ملحوظا في كلا من متوسط حجم الكريات الدم الحمراء MCV و MCH و كان متوسط القيمة في مرضى ما قبل الغسيل الي ما بعد الغسيل (p < 0.0001) , والانخفاض يشمل ايضا كريات الدم البيضاء وكان متوسط قيمة خلايا الدم البيضاء في ما قبل غسيل الكلى الي ما بعد الغسيل( 0.0045 P- Value). أن الدرجات المختلفة في المتغيرات الدموية لدى المرضى المصابين بأمراض الكلى و الخاضعين لغسيل الكلى تحتاج إلى تقييم ومتابعة , و التقييم الروتيني لهذه المعايير مهم في العلاج ويمكن أن يساعد في خفض معدلات الإصابة والوفيات